Beyond innocence: the life sentence of Darryl Hunt : a true story of race, wrongful conviction, and an American reckoning still to come - Zerwick, Phoebe (Atlantic Monthly Press)
In May 1985, Darryl Hunt, a Black teenager in Winston-Salem, N.C. was falsely convicted and sentenced to life in prison for the rape and murder of a young white copyeditor at the local paper. In 2003, an award-winning series of articles led to the DNA evidence that exonerated Hunt. Part true crime drama, part chronicle of a remarkable life cut short by systemic prejudice, this book powerfully illuminates the sustained catastrophe faced by an innocent person in prison and the civil death every ex-prisoner experiences attempting to restart their lives